SAFETY OF AMIODARONE USAGE IN PATIENTS WITH WOLFF-PARKINSON-WHITE SYNDROME AND ATRIAL FIBRILLATION - D. A. Kuzhel; G. V. Matyushin; E. A. Savchenko (Рациональная фармакотерапия в кардиологии, 2016)
Amiodarone is one of the basic antiarrhytmic drugs for atrial fibrillation treatment. However application of amiodarone in patients with atrial fibrillation and Wolff-Parkinson-White syndrome can induce ventricular fibrillation. Amiodarone usage in these patients should be accompanied by readiness for performance of resuscitation. This is confirmed by clinical case presentation.